Interpretation of The Characteristics of The Novel Ronggeng Dukuh Paruk by Ahmad Tohari - Mafulla, Anies; Jaya, Wayan Satria; Wicaksono, Andri; Hastomo, Tommy (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2020)
Literature is a reflection of the reality of people's lives that need to be understood and taken advantage of by many people. Therefore, it is necessary to conduct a study or analysis to take the benefits in literary works. The novel of Ronggeng Dukuh Paruk is a literary work that presents a person's life with society and highlights the character or nature of each actor. This study aims to interpret the characters and characterizations contained in the novel Ronggeng Dukuh Paruk by Ahmad Tohari. The method used in this study is a qualitative research method. Collecting data in this study using observation techniques and documentation techniques and the data analysis technique used reading technique. The results showed that the character in the novel, namely Rasus, had various characterizations. So, understanding the story in this novel, the reader will benefit from studying a person's character from his tone of voice in order to be able to understand situations and conditions in social life.